STABILIZER CONCENTRATION AND SUCROSE TO THE VELVA TOMATO FRUIT QUALITY - Kartika Dewi, Rini (Jurnal Teknik Kimia, 2010)
Tomato is a plants that easy to find and is rich in vitamins C, A, minerals, fiber and phytonutrientssubstances. The benefits of a tomato is can be used as a extra flavor for food, sauces, candied dried, juice, totreat digestive disorders, diarrhea, and can also be used in the beauty industry. In general, tomato susceptibleto damage caused by several factors such as physiological factors, physical, microbiological and chemical sothat such damage can lead to a decreased quality and economic value. To reduce such damage one of thealternatives is using tomato as a raw material in the manufacture of Velva Fruit. Velva Fruit is a kind offrozen food ice cream made from fruits and has an advantage for it low fat level because it isn’t using milk fatand contain lots of fiber and vitamin C. The method is using tomato that has been sorted, washed, blanching,and crushed with blender. Then the tomato juice was mixed with Sucrose, citric acid and stabilizer (CMC).Dough mixture is then cooled at 4 ° C for 24 hours and performed freezing (Hardening) for 24 hours at 10°C.Key words: Velva fruit, tomatoes,vitamin, C, vitamin A, phytonutrients substances